Man, Nature and Ocean - an Ecology Perspective of Coastal Ecosystem of Sundarbans Forests - Chakrabarti, Kalyan (Indian Forester, 1999)
In this paper, various intricate environmental imperatives have been stated for the coastal ecosystem of Sundar bans. The development ofthe area lies in maintenance of ecological balance in the fragile ecosystem. The low plant-animal diversity for Sundarbans is clearly a warning signal for ensuring strict protection of this biotope from the future impending disasters. This conservational exercise will be of considerable help to reconsider and reorient the broad conservation strategy of Sundarbans Mangroves. Sundarbans Mangrove inhabit higher caloric concentrations and significantly high biomass productivity with low generic and specific diversity generally for both flora and fauna. Because of locational advantages of Mangroves of Indian Sundarbans, biotic interference is least in Sundarbans in comparison to other forest types of West Bengal. The balance ofpobr floral and faunal diversity in Sundarbans Mangroves is practically recompensed by lesser biotic interference. So with proper balanced forest management, Sundarbans hold bright potentiality in natural ecosystems. This unique conservational exercise is likely to open up new dimension into unknown properties of Sundarbans Mangrove ecosystem of West Bengal.